Molecular and Clinical Characterization of Chikungunya Virus Infections in Southeast Mexico - Galán Huerta, Kame Alberto; Martínez Landeros, Erik; Delgado Gallegos, Juan Luis; Caballero Sosa, Sandra; Malo García, Iliana Rosalía; Fernández Salas, Ildefonso; Ramos Jiménez, Javier; Rivas Estilla, Ana María (Molecular Diversity Preservation International, 2018)
Chikungunya fever is an arthropod-borne infection caused by Chikungunya virus (CHIKV). Even though clinical features of Chikungunya fever in the Mexican population have been described before, there is no detailed information. The aim of this study was to perform a full description of the clinical features in confirmed Chikungunya-infected patients and describe the molecular epidemiology of CHIKV. We evaluated febrile patients who sought medical assistance in Tapachula, Chiapas, Mexico, from June through July 2015. Infection was confirmed with molecular and serological methods. Viruses were isolated and the E1 gene was sequenced. Phylogeny reconstruction was inferred using maximum-likelihood and maximum clade credibility approaches. We studied 52 patients with confirmed CHIKV infection. They were more likely to have wrist, metacarpophalangeal, and knee arthralgia. Two combinations of clinical features were obtained to differentiate between Chikungunya fever and acute undifferentiated febrile illness. We obtained 10 CHIKV E1 sequences that grouped with the Asian lineage. Seven strains diverged from the formerly reported. Patients infected with the divergent CHIKV strains showed a broader spectrum of clinical manifestations. We defined the complete clinical features of Chikungunya fever in patients from Southeastern Mexico. Our results demonstrate co-circulation of different CHIKV strains in the state of Chiapas.